STRATEGI PENYELESAIAN SENGKETA PULAU ANTARA KABUPATEN ACEH SINGKIL PEMERINTAH ACEH DENGAN KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - Ardi Eko Wijoyo; Neneng Sri Rahayu; Hamka (Halu Oleo University, 2024)
Aceh Singkil Regency and Central Tapanuli Regency are fighting over four islands, namely Mangkir Gadang Island, Mangkir Ketek Island, Lipan Island and Panjang Island. This research aims to analyze the factors that caused the island dispute between Aceh Singkil Regency and Central Tapanuli Regency. The factors analyzed are factors obtained from interviews and field observations as well as based on previous research studies. This research uses a descriptive qualitative approach method with data collection using interviews and field observations. Meanwhile, the analysis process uses boundary-making theory and in strategy formulation uses weighting. The research results show that the island dispute between Aceh Singkil Regency and Central Tapanuli Regency has been going on for a long time without a final decision. Research identifies the causes of disputes including juridical, economic, historical, social, community service and geographic factors. To overcome this problem, the recommended strategies include preparing SOPs for resolving island disputes, strengthening procedures and revising the Minister of Home Affairs Decree regarding regional codes and data, as well as strengthening the leadership's understanding of dispute resolution. The main priority is preparing SOPs, while the last priority is strengthening leadership understanding.